2018
DOI: 10.1007/s12034-017-1522-x
|View full text |Cite
|
Sign up to set email alerts
|

Crosslinked poly(ether ether ketone): cost-effective proton exchange membranes for fuel cell application

Abstract: Sulphonated poly(ether ether ketone) copolymers bearing pendant carboxylic acid (SPEEK-C) have been synthesized via nucleophilic condensation reaction of 4,4-difluorobenzophenone, sulphonated 4,4-difluorobenzophenone and 3,5-dihydroxy benzoic acid. The structure of the sulphonated copolymer was identified from FT-IR and 1 H-NMR spectrum. The pendant carboxylic groups of SPEEK-C were further crosslinked with poly(vinyl alcohol) (PVA) to fabricate the crosslinked (SPEEK/PVA) membranes. The performance of the mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…Table S2 also summarizes the LOI values of all prepared membranes. Awasthi et al 49 . reported that polymer membranes with LOI values greater than 26 are considered to have self‐extinguishing behavior.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table S2 also summarizes the LOI values of all prepared membranes. Awasthi et al 49 . reported that polymer membranes with LOI values greater than 26 are considered to have self‐extinguishing behavior.…”
Section: Resultsmentioning
confidence: 99%
“…Table S2 also summarizes the LOI values of all prepared membranes. Awasthi et al 49 reported that polymer membranes with LOI values greater than 26 are considered to have selfextinguishing behavior. The f-CNTs/f-CNDs based composite membranes do exhibit LOI values greater than 26 which proves their flame retardant nature.…”
Section: X-ray Diffraction Studies Of Membranesmentioning
confidence: 99%
See 1 more Smart Citation
“…The monomer was synthesized according to the method reported by Chen and Awasthi; some modifications had been added. 36,37 4,4′-dichlorodiphenylsulfone (14.358 g, 50 mmol) and 30 ml fuming sulfuric acid (20% SO 3 ) were placed in a round bottom flask and the solution was stirred at 40 • C to dissolve; an amber homogeneous transparent solution was obtained. The mixture was slowly heated to 110 • C and held at this temperature for 10 h. After heating, the mixture was cooled down to room temperature and 370 ml ice water was added.…”
Section: Synthesis Of 33′-disulfonated-44′dichlorodiphenyl Sulfone (S...mentioning
confidence: 99%
“…Also, due to the structural and morphological differences, the random copolymers shows the difference in exchange capacities (IEC) which influence the stability and conductivity of membranes. [15][16][17][18] Therefore, the present study aimed to develop multiblock copolymer membranes, which could exhibit well-defined nanophase morphologies, display better hydrolytic stability and facilitate high proton conductivity with a well-connected hydrophobic segment that could also provide dimensional stability and durability. The possibility of randomization of hydrophilic-hydrophobic arrangement at high reaction temperatures as reported by James E. McGrath et al, 2008, was addressed by end-capping the phenoxide telechelic functionality bearing hydrophobic oligomer by highly reactive perfluorinated end group, decafluorobiphenyl (DFBP) monomer.…”
mentioning
confidence: 99%